A Matrix Representation of Outer Derivations from $\frak{gl}_{0|2}$ to the Generalized Witt Lie Superalgebra (Communications in Mathematical Research, 2019)
Let $\frak{gl}_{0|2}$ be a subalgebra of the general linear Lie superalgebra. Inthis paper, outer derivations from $\frak{gl}_{0|2}$ to the generalized Witt Lie superalgebra arecompletely determined by matrices.
Keywords: outer derivation; inner derivation; matrix representation; generalized Witt Lie superalgebra.